How do medical students deal with the topic of racism? A qualitative analysis of group discussions in Germany. - Simon Matteo Gerhards; Mark Schweda (PLoS ONE)
Background Anti-racism is part of the medical professional ethos. Nevertheless, racism pervades medicine on individual, institutional, and structural levels. The concept of habitus helps to understand deficiencies in enacting anti-racism in practice. We use a habitus-based framework to analyse how medical students in Germany deal with the topic of racism. The research questions are: What are medical students' understandings of racism? How do they deal with the topic in discussions? What difficulties do they face in such discussions? Methods In a qualitative-explorative research design, we conducted six online group discussions with 32 medical students from medical schools all over Germany. Data analysis combined qualitative methods from thematic qualitative content analysis and the documentary method. Results We identified five typical ways of dealing with the topic of racism in discussions. The first one ('scientistic') orientates action towards the idea of medicine as an objective science, justifies the use of racial categories as scientific, and defines racism based on intention. The second ('pragmatic') orientates action towards tacit rules of clinical practice, justifies the use of racialised categories as practical and defines racism as an interpersonal problem. The third ('subjectivist') lacks a clear orientation of action for dealing with the topic of racism and instead displays uncertainty and subjectivism in understanding racialised categorisations as well as racism. The fourth ('interculturalist') orientates action towards an ideal of intercultural exchange, understands racialised categorisations as representing cultural differences and interprets racism as prejudice against cultures. The fifth ('critical') orientates action towards sociological scholarship, understands racialised categorisations as social constructs and views racism as a structural problem. Conclusion The results presented help to understand preconditions of enacting anti-racism in medicine and point to difficulties and learning needs. The heterogenous ways of dealing with the topic require a differentiated approach in medical education.